A novel electromagnetic tracking system for surgery navigation - Filippo Attivissimo; Anna Maria Lucia Lanzolla; Sabatina Carlone; Pietro Larizza; Gioacchino Brunetti (Computer Assisted Surgery, 2018)
Objective: This paper proposes the development of a novel electromagnetic tracking system for navigation surgery. Main objective is to provide a system able to operate in a wide tracking volume to make easier and efficient the surgical procedures by assuring high measurement accuracy. Methods: A new field generator consisting in five transmitting coils excited with Frequency Division Multiplexing technique has been developed. Attention is devoted to designing and arrangement of the coils to assure high sensitivity, system scalability and a homogeneous magnetic field inside working volume. A suitable technique based on Look-Up-Table is applied for sensor position calculation and an anthropomorphic robot is used for table calibration. Results: Experimental tests highlight a good repeatability of the measurement data and a negligible noise influence for the proposed system. The obtained tracking volume is wider with respect to the commercial tracking device used in surgical applications and seem promising. Conclusion: The main characteristic of the developed system consists of: scalable and modular configuration of Field Generator, high measured sensitivity due to the increased number of transmitting coils with respect to the classical configuration and large tracking volume. The development of the proposed magnetic tracking systems with high accuracy and wide working volume allows to promote broader utilization of advantaged techniques in surgery procedures for both improving the effectiveness and decreasing the invasiveness of medical interventions.